STOCHASTIC FRONTIER ANALYSIS (SFA): PENGUKURAN EFISIENSI DIREKTORAT JENDERAL PAJAK (DJP) DALAM PENGELOLAAN DANA PAJAK - Ratna Herawati; Risanda A. Budiantoro; Amalia Nur Chasanah (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2021)
This study aims to measure technical efficiency and identify factors that affect efficiency of Direktorat Jenderal Pajak (DJP) (consists of 33 DJP’s Regional Offices and one DJP’s Head Office) in managing tax funds on receipt. Data that we use are time unbalanced panel data from 2012 until 2019. The input variables used are total assets and operational costs, while the output variables are the receipt of pajak funds. Using stochastic frontier analysis, this study has successfully identified that total assets and operational costs had a a positive and significant effect on receipt of pajak funds. Overall, technical efficiency in receipt of pajak funds of DJP are found to be 86,63 percent, which means there are about 13,36 percent that can still be optimized.Keywords : Direktorat Jenderal Pajak (DJP), Stochastic Frontier Analysis, Technical Efficiency